Ներդրումային միջավայրի դերը և գնահատման առանձնահատկությունները - Հայկ Մխիթարյան (ՀՀ ԳԱԱ հրատ.)
В последние десятилетия роль международных потоков инвестиционного капитала становится более значительной, чем мировая торговля товарами и услугами. В конечном счете международные потоки капитала способствуют тому, что национальные экономики становятся более зависимыми от них. Таким образом, на нынешнем этапе экономического развития одним из основных задач любого государства является обеспечение необходимых условий для формирования благоприятной инвестиционной среды, так как последняя является важной гарантией для безопасного и устойчивого экономического роста. In recent decades, the role of international capital flows is more important than global trade in goods and services. The movement o money for investing, trade or business production, whether by a corporation, a goverment or an individual, is commonly referred to as capital flows. Ultimately, international capital flows are contributed to the fact that the national economy becomes more dependent on them. Thus, in the present stage of economic development, one of the main tasks of any state is to ensure the necessary conditions for the formation of a favorable investment environment, as the latters, that, it is an important guarantee for safe and sustainable economic growth.
Keywords: Social Sciences; Economic Theory